Diversity and the Composition of Fatty Acids of Lipolytic Bacteria Isolated from Soil and Aquatic Sediment in a Forest and on an Oil Palm Plantation - Wijayanti, Marini; Meryandini, Anja; Wahyudi, Aris Tri; Yuhana, Munti (UI Scholars Hub, 2014)
The specific bacteria in forests and on oil palm plantations are lipolytic bacteria. Their enzymes have been applied in the agro-aquaculture, food, detergent, pharmaceutical, dairy, and biodiesel-biokerosene industries. This study describes the diversity of cultivable lipolytic bacteria from soil and aquatic sediment in a forest and on an oil palm plantation and their fatty acid products. Soil samples used in this research were obtained from topsoil in a lowland forest and on an oil palm plantation and from sediments in fresh water near these sites. The forest is located in Bukit Duabelas National Park, and the oil palm plantation is near the forest in Sarolangun District, Jambi Province, Indonesia. Twenty-two isolates of lypolitic bacteria were selected from 32 isolates grown in lipolytic selective medium. The 22 consisted of 11 isolates from topsoil and 11 from aquatic sediment from the forest and plantation area. These isolates were identified by 16S rRNA-sequence data analysis. Taxonomically, they belonged to five genera: Burkholderia, Cupriavidus, Serratia, Acinetobacter, and Kurthia. The maximum likelihood tree showed that they are phylogenetically distributed in three clusters. They were clustered into three groups: the Burkholderia-Cupriavidus group, the Serratia-Acinetobacter group, and the Kurthia group. Their lipolytic enzymes formed various fatty acids after analysis by gas chromatography-flame ionization detector (GC-FID). Some isolates formed essential fatty acids, such as linoleic, linolenic, arachidonic, eicosapentanoic acid (EPA), and docosahexanoic acid (DHA).